High-heat-conductivity ceramic / metal joint and preparation method thereof
By adding a foam silver intermediate layer to the active brazing method, the problem of low thermal conductivity of DBC or DBA produced by the active brazing method is solved, and the high thermal conductivity of the ceramic/metal joint is achieved, and the welding interface and tissue are uniform and defect-free.
Patent Information
- Application Number
- CN202510331133.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-29
AI Technical Summary
DBC or DBA produced by active brazing has low thermal conductivity and cannot meet the demand for high-thermal conductive materials of electronic equipment.
By adding a foam silver intermediate layer between the upper brazing foil and the lower brazing foil, wetting and filling the foam silver after melting the solder at a specific high temperature, weaving and filling the foam silver is achieved, and welding between ceramics and metals is achieved, and the thermal conductivity of the weld is improved by using foam silver as a high thermal conductivity channel in the weld.
The thermal conductivity of the ceramic/metal joint is improved, and DBC or DBA with high thermal conductivity is obtained, and the welding interface is tightly bonded, and the tissue distribution in the weld is evenly distributed without obvious defects.
Smart Images

Figure CN119897540A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding, and in particular to a high thermal conductivity ceramic / metal joint and a preparation method thereof. Background Art
[0002] As electronic devices develop towards miniaturization, functional integration, compact structure, high power density, and stability and reliability, the heat flux density of the core chips of electronic devices has increased significantly. Faced with ultra-high heat flux density, the thermal control problem of the core chips has become prominent, and their service life and reliability have decreased exponentially. Statistics show that when the temperature of electronic devices rises from 80°C to 120°C, the power drops by at least 30%. When the temperature exceeds 160°C, the reliability decreases by 10 times for every 1°C increase. Direct copper-bonded ceramic substrates (DBC) or direct aluminum-bonded ceramic substrates (DBA) have become important electronic packaging materials due to their good thermal and electrical conductivity, especially in power modules (IGBT) and integrated power electronic modules.
[0003] During the operation of the IGBT module, a large amount of heat generated on the chip surface needs to be transferred to the module heat dissipation base plate through the substrate, and then conducted to the radiator through the thermal grease on the base plate to complete the overall heat dissipation flow of the module. Therefore, the substrate is required to have excellent thermal conductivity. At present, among the preparation methods of DBC or DBA, active brazing is one of the most widely studied and most suitable connection methods. This is because active brazing has the advantages of strong brazing material designability, less impact on the parent material, large welding area, and the ability to achieve complex welding joints. The brazing material system uses active elements to directly weld ceramic materials and metals. This method mainly uses the active elements to react with ceramics at the interface to form a compound layer to improve the wettability of diamond, and the welding process is relatively simple. However, in the related art, the thermal conductivity of DBC or DBA prepared by active brazing is low and needs to be further improved. Summary of the invention
[0004] The problem solved by the invention is that the thermal conductivity of DBC or DBA prepared by active brazing is low.
[0005] In order to solve the above problems, the present invention provides a method for preparing a high thermal conductivity ceramic / metal joint, comprising:
[0006] Step S1, assembling the ceramic to be welded, the upper brazing material foil, the foamed silver, the lower brazing material foil and the metal substrate in order from top to bottom to obtain an assembly;
[0007] Step S2, under a preset vacuum degree, heating the assembly to a preset temperature at a preset heating rate, keeping the temperature for a preset time, and cooling to room temperature at a preset cooling rate to obtain a ceramic / metal joint.
[0008] Optionally, in step S1, the thickness of the foamed silver is 0.1 mm to 1 mm, the porosity is 80% to 90%, and the pore size is 30 μm to 200 μm.
[0009] Optionally, in step S1, the material of the ceramic to be welded is selected from one of sapphire, aluminum nitride, gallium carbide, diamond and silicon carbide.
[0010] Optionally, in step S1, the material of the metal substrate is selected from one of a copper alloy and a titanium alloy.
[0011] Optionally, in step S1, the material of the upper solder foil and the lower solder foil is independently selected from one of Ag-Cu-Ti alloy, Ag-Cu-In-Ti alloy, Ag-Cu-Sn-Ti alloy and Au-Cu alloy.
[0012] Optionally, in step S1, the thickness of the upper solder foil and the lower solder foil are both 0.05 mm to 0.5 mm.
[0013] Optionally, in step S2, the preset vacuum degree is lower than 10 -4 Pa.
[0014] Optionally, in step S2, the preset heating rate is 5°C / min to 20°C / min, the preset temperature is 600°C to 860°C, and the preset time is 10min to 30min.
[0015] Optionally, in step S2, the preset cooling rate is 5°C / min to 10°C / min.
[0016] The present invention also provides a high thermal conductivity ceramic / metal joint, which is made by the above-mentioned preparation method of the high thermal conductivity ceramic / metal joint.
[0017] Compared with the related art, in the preparation method of the high thermal conductivity ceramic / metal joint provided by the invention, by adding a foamed silver intermediate layer between the upper brazing material foil and the lower brazing material foil, the brazing material is melted at a specific high temperature and then wetted and filled with foamed silver, and the welding of the parent materials on both sides (ceramic to be welded and metal substrate) is achieved at the same time. After the welded joint is solidified, the foamed silver serves as a high thermal conductivity channel in the weld, thereby improving the thermal conductivity of the weld to obtain a ceramic / metal joint (DBC or DBA) with higher thermal conductivity. In summary, by adopting the method of the present invention, a DBC or DBA with higher thermal conductivity can be obtained, and the welding interface is tightly bonded, the tissue distribution in the weld is uniform, and there are no obvious defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Schematic diagram of the process of preparing a high thermal conductivity ceramic / metal joint according to an embodiment of the present invention;
[0019] Figure 2 Schematic diagram of the structure of the assembly in the embodiment of the present invention.
[0020] Description of reference numerals:
[0021] 1. Ceramic to be welded; 2. Upper solder foil; 3. Foamed silver; 4. Lower solder foil; 5. Metal substrate. DETAILED DESCRIPTION
[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. Although certain embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be interpreted as being limited to the embodiments described herein. On the contrary, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the drawings and embodiments of the present invention are only for exemplary purposes and are not intended to limit the scope of protection of the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0024] The term "including" and its variations used in this article are open inclusions, that is, "including but not limited to"; the term "based on" is "based at least in part on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one other embodiment"; the term "some embodiments" means "at least some embodiments"; the term "optionally" means "optional embodiments". The relevant definitions of other terms will be given in the following description. It should be noted that the concepts of "first" and "second" mentioned in the present invention are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship. In addition, the terms "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, the meaning of "multiple" is two or more.
[0025] In view of the problems existing in the above-mentioned related technologies, such as Figure 1 As shown, this embodiment provides a method for preparing a high thermal conductivity ceramic / metal joint, comprising:
[0026] Step S1: Figure 2 As shown, the ceramic to be welded 1, the upper brazing material foil 2, the foamed silver 3, the lower brazing material foil 4 and the metal substrate 5 are assembled in sequence from top to bottom to obtain an assembly;
[0027] Step S2, under a preset vacuum degree, heating the assembly to a preset temperature at a preset heating rate, keeping the temperature for a preset time, and cooling to room temperature at a preset cooling rate to obtain a ceramic / metal joint.
[0028] In the preparation method of the high thermal conductivity ceramic / metal joint provided in the embodiment of the invention, a foamed silver intermediate layer is added between the upper brazing material foil 2 and the lower brazing material foil 4, and the brazing material is melted at a specific high temperature to wet and fill the foamed silver, and the welding of the parent materials on both sides (ceramic 1 to be welded and metal substrate 5) is achieved at the same time. After the welded joint is solidified, the foamed silver serves as a high thermal conductivity channel in the weld, thereby improving the thermal conductivity of the weld to obtain a ceramic / metal joint (DBC or DBA) with higher thermal conductivity. In summary, by using the method of the embodiment of the present invention, a DBC or DBA with higher thermal conductivity can be obtained, and the welding interface is tightly bonded, the tissue distribution in the weld is uniform, and there are no obvious defects.
[0029] The porosity of the silver foam 3 is too low, which is not conducive to the filling of the silver foam pores after the solder melts. The pore size of the silver foam 3 is too small, which is not conducive to the filling of the solder. If the pore size is too large, the proportion of the silver foam in the weld structure is reduced, and the effect of improving the thermal conductivity of the ceramic / metal joint is reduced. Therefore, in order to further improve the thermal conductivity of the ceramic / metal joint; in some embodiments of the present invention, in step S1, the thickness of the silver foam 3 is 0.1mm to 1mm, the porosity is 80% to 90%, and the pore size is 30μm to 200μm.
[0030] In some embodiments of the present invention, in step S1, the material of the ceramic 1 to be welded is selected from one of sapphire, aluminum nitride, gallium carbide, diamond and silicon carbide.
[0031] In some embodiments of the present invention, in step S1, the material of the metal substrate 5 is selected from one of a copper alloy and a titanium alloy. Exemplarily, the copper alloy is C51000, and its components include, by weight percentage: Cu: 88%, Sn: 12%.
[0032] In some embodiments of the present invention, in step S1, the materials of the upper solder foil 2 and the lower solder foil 4 are independently selected from one of Ag-Cu-Ti alloy, Ag-Cu-In-Ti alloy, Ag-Cu-Sn-Ti alloy and Au-Cu alloy. Exemplarily, by weight percentage, the components of the Ag-Cu-Ti alloy include: Ag: 70.5%, Cu: 26.5%, Ti: 3%.
[0033] In some embodiments of the present invention, in the step S1, the thickness of the upper solder foil 2 and the lower solder foil 4 are both 0.05 mm to 0.5 mm.
[0034] In some embodiments of the present invention, in step S2, the preset vacuum degree is lower than 10-4Pa, the preset heating rate is 5°C / min to 20°C / min, the preset temperature is 600°C to 860°C, and the preset time is 10min to 30min; in step S2, the preset cooling rate is 5°C / min to 10°C / min.
[0035] The present invention is further described below in conjunction with specific embodiments.
[0036] Example 1
[0037] A1. Assemble the ceramic to be welded, the upper solder foil, the foamed silver, the lower solder foil and the metal substrate in order from top to bottom to obtain an assembly; wherein the ceramic to be welded is made of diamond with a thickness of 5 mm; the foamed silver is 0.5 mm thick, has a porosity of 85% and a pore size of 100 μm; the upper solder foil and the lower solder foil are both made of Ag-Cu-Ti alloy; the thickness of the upper solder foil and the lower solder foil are both 1 mm; by weight, the components of the Ag-Cu-Ti alloy include: Ag: 70.5%, Cu: 26.5%, Ti: 3%; the metal substrate is made of copper alloy C51000 with a thickness of 5 mm.
[0038] Step S2, under a preset vacuum degree, heating the assembly to a preset temperature at a preset heating rate, keeping the temperature for a preset time, and cooling to room temperature at a preset cooling rate to obtain a ceramic / metal joint; the preset vacuum degree is 10 -5 Pa, the preset heating rate is 10°C / min, the preset temperature is 730°C, and the preset time is 20min; in step S2, the preset cooling rate is 7.5°C / min.
[0039] Example 2
[0040] The difference from Example 1 is that in step A1, the thickness of the foamed silver is 0.5 mm, the porosity is 80%, and the pore size is 200 μm.
[0041] Example 3
[0042] The difference from Example 1 is that in step A1, the thickness of the foamed silver is 0.5 mm, the porosity is 90%, and the pore size is 30 μm.
[0043] Comparative Example 1
[0044] The difference from Example 1 is that step A1 is: assemble the ceramic to be welded, the upper solder foil, the lower solder foil and the metal substrate in sequence from top to bottom to obtain an assembly; wherein the material of the ceramic to be welded is diamond, and the thickness is 5 mm; the materials of the upper solder foil and the lower solder foil are both Ag-Cu-Ti alloy; the thickness of the upper solder foil and the lower solder foil are both 1 mm; in terms of weight percentage, the components of the Ag-Cu-Ti alloy include: Ag: 70.5%, Cu: 26.5%, Ti: 3%; the material of the metal substrate is copper alloy C51000, and the thickness is 5 mm.
[0045] Comparative Example 2
[0046] The difference from Example 1 is that in step A1, the thickness of the foamed silver is 0.5 mm, the porosity is 85%, and the pore size is 220 μm.
[0047] Experimental example
[0048] The thermal conductivity of the ceramic / metal joints prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the results are shown in Table 1. It can be seen from Table 1 that compared with Comparative Examples 1 to 2, the ceramic / metal joints prepared in Examples 1 to 3 have higher thermal conductivity.
[0049] Table 1
[0050]
[0051] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity ceramic / metal joint, characterized in that: include: Step S1, assembling the ceramic to be welded (1), the upper brazing material foil (2), the foamed silver (3), the lower brazing material foil (4) and the metal substrate (5) in order from top to bottom to obtain an assembly; Step S2, under a preset vacuum degree, heating the assembly to a preset temperature at a preset heating rate, keeping the temperature for a preset time, and cooling to room temperature at a preset cooling rate to obtain a ceramic / metal joint.
2. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S1, the thickness of the foamed silver (3) is 0.1 mm to 1 mm, the porosity is 80% to 90%, and the pore size is 30 μm to 200 μm.
3. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S1, the material of the ceramic (1) to be welded is selected from one of sapphire, aluminum nitride, gallium carbide, diamond and silicon carbide.
4. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S1, the material of the metal substrate (5) is selected from one of a copper alloy and a titanium alloy.
5. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S1, the materials of the upper solder foil (2) and the lower solder foil (4) are independently selected from one of Ag-Cu-Ti alloy, Ag-Cu-In-Ti alloy, Ag-Cu-Sn-Ti alloy and Au-Cu alloy.
6. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S1, the thickness of the upper solder foil (2) and the lower solder foil (4) are both 0.05 mm to 0.5 mm.
7. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In step S2, the preset vacuum degree is lower than 10 -4 Pa.
8. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S2, the preset heating rate is 5°C / min to 20°C / min, the preset temperature is 600°C to 860°C, and the preset time is 10min to 30min.
9. The method for preparing a high thermal conductivity ceramic / metal joint according to claim 1, characterized in that: In the step S2, the preset cooling rate is 5°C / min to 10°C / min.
10. A high thermal conductivity ceramic / metal joint, characterized in that: The high thermal conductivity ceramic / metal joint is manufactured by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Ceramic and metal brazing composite component and preparing method thereof
CN105537712A
High-temperature brazing filler metal preparing method based on foamed silver filled with metal tin
CN106216873A
Auxiliary brazing method for CuO nano structure enhanced foam copper intermediate layer
CN107570830A
Method for connecting ceramic cover for antenna and metal connecting ring
CN113000960A
All-metal sintering power module interconnection method
CN113594053A
Cited By
Welding method of aluminum nitride ceramic heating plate for semiconductor equipment
CN121107873A